2018
DOI: 10.1002/chem.201803664
|View full text |Cite
|
Sign up to set email alerts
|

Homo‐ and Heteroleptic Coordination Polymers and Oxido Clusters of Bismuth(III) Vinylsulfonates

Abstract: The synthesis and characterization of six homo- and heteroleptic coordination polymers and oxido clusters of bismuth(III) vinylsulfonates are reported. The solvent-mediated reaction of BiPh and vinylsulfonic acid in ethanol produces [{Ph Bi(O SCH=CH )} ] (1), which crystallizes as a one-dimensional coordination polymer as a result of bridging sulfonato ligands accompanied by intermolecular Bi⋅⋅⋅ π(arene) London dispersion interactions. In solution, compound 1 equilibrates to give [{PhBi(O SCH=CH ) } ] (2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 142 publications
0
8
0
Order By: Relevance
“…The main reflection corresponds to the interlayer distance, assuming a closed, packed nanocluster arrangement [ 20 , 50 ]. Thus, an interlayer distance for 2 of 1.975 nm (2 θ = 4.47°) was calculated using Bragg’s equation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reflection corresponds to the interlayer distance, assuming a closed, packed nanocluster arrangement [ 20 , 50 ]. Thus, an interlayer distance for 2 of 1.975 nm (2 θ = 4.47°) was calculated using Bragg’s equation.…”
Section: Resultsmentioning
confidence: 99%
“…These so-called bismuth subnitrates were recently studied in order to elucidate the molecular mechanisms of the condensation that lead to the formation of bismuth oxido nitrates with up to 38 bismuth atoms, e.g., in the nanoscaled [Bi 38 O 45 (NO 3 ) 24 ], using a combined in situ small-angle X-ray scattering (SAXS) and pair distribution function (PDF) analysis approach, as well as electrospray ionization mass spectrometry (ESI-MS) [ 16 , 17 , 18 ]. The Bi 38 O 45 core seems to be the most stable one among the bismuth oxido clusters, and various molecules of this type were reported recently, including sulfonates, salicylates, nitrates, and methacrylates [ 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 ]. However, most of them suffer from either low hydrolytic stability at the ligand periphery, low solubility, low biocompatibility of their ligands, or accessibility on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…The trans angles in the equatorial ОBiO plane are 177. The synthesis and characteristics of two coordination polymers of vinylbismuth(III) sulfonates were reported [64]. The bismuth complexes were synthesized from triphenylbismuth and vinylsulfonic acid in ethanol or acetonitrile (Scheme 55).…”
Section: Scheme 54mentioning
confidence: 99%
“…An umber of other authors have invokeds imilar arguments to explain unusualg eometries found in avariety of other bismuth compounds. [20][21][22] The only reasonablyc lose interaction that the bismuth centreo f2a does make is with disordered H20B/F at ad istance of 3. The formation of such ac ontactd oes support the presence of as tereochemically activel one pair on bismuth.…”
Section: Introductionmentioning
confidence: 99%